Aeroengines: Principles, Components, and Eco-friendly Trends - Sheikhi, Mohammad Rauf; Aygun, Hakan; Altuntas, Onder (Springer Nature, 2022)
The expectation of increased air travel in the future decades is met with the issue of a growing environmental effect. The aviation sector is developing potential solutions to reduce the environmental effect. Gas turbine engines are still the most common type of engine used in aircraft, and due to population growth and the number of flights, the emissions produced by these engines have become a major challenge in their future application. The use of lightweight materials is a powerful option to reduce fuel consumption and thus reduce aviation emissions. This chapter gives a brief history of aircraft engines, their classification, principles, common materials used in the main components, and the environmental effects of aircraft engine materials. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2022.
Keywords: Adaptive cycle engine; Aeroengines; Eco-friendly trends